ADSORÇÃO DE CORANTES TÊXTEIS POR CARVÃO ATIVADO PREPARADO A PARTIR DO AGUAPÉ (Eichhornia crassipes) - Lucena, Júlio Evangelista de (2014)
Activated carbon produced from water hyacinth (CAA) was used for the adsorption of textile dye Remazol Turquoise and Violet Remazol aqueous solutions. ZnCl₂ was used as the activating agent in the impregnation ratio (2:1) and pyrolysis was at 700 ° C under N₂ flow, resulting in a surface area with CAA 640 m² gˉ¹. The adsorbent was characterized, and analysis of the surface area by the BET method, by elemental analysis, vibrational spectroscopy in the infrared region, Boehm titration method, which quantified the phenolic, carboxylic and lactonic groups groups on the carbon surface, thermogravimetric analysis, diffraction the x rays and point of zero charge (PZC). Factors affecting adsorption, such as pH, equilibration time, concentration of adsorbate and temperature were estudied in batch system. The activated carbon showed better adsorption rate at pH's in the acidic range. The kinetic data were fitted to models Elovich, pseudo first order and pseudo-second order, which the Elovich model showed better fit. Adsorption isotherms were measured and fitted to Langmuir and Freundlich models, where the latter provided better fit to the experimental data. The thermodynamic data obtained by evaluation of the isotherms at temperatures of 10, 25, 35, 45 and 55 ° C, indicated that the adsorptive process is endothermic, spontaneous and favorable. The CAA proved ultimately to be a good alternative in the adsorption of the dyes studied, it showed a low production cost and a high rate of removal.